Application of powdered dutch cheese in wheat flour bread technology - Bilyk, Olena; Burchenko, Liudmila; Bondarenko, Yuliia; Bilokhatniuk, Volodymyr; Bilokhatniuk, Vasyl (My University, 2025)
Bakery products made from wheat flour occupy a leading position in the assortment. Consumption of such products in the amount of the daily norm (277 g) allows to provide a person’s daily protein requirement by 40.0–43.0%. Wheat bread is a basic product in the diet of the majority of the population, therefore there is an objective need to expand its assortment with products with increased nutritional value, as well as to diversify its taste properties through the use of additional non-traditional raw materials. The object of research is the technology of bread from wheat flour using powdered Dutch cheese to increase the nutritional value and consumer characteristics of the finished product. It was established that powdered Dutch cheese is characterized by a good dissolution rate, low tendency to lump formation and a whiteness index corresponding to high-grade flour. The chemical composition of dry hard cheese is mainly represented by protein and fat, which will contribute to the enrichment of bakery products with milk proteins and milk fat. It was established that according to the complex quality indicator, the optimal dosage of powdered Dutch cheese in the recipe for wheat flour bread is 4.0% by weight of flour. At such a dosage, a bright color of the crust of the product and a lighter color of the crumb are noted compared to the control. The bread acquires a pleasant creamy taste and aroma. It was established that in the case of dosing powdered Dutch cheese in an amount of 4.0% by weight of flour, the fermentation process is intensified, gluten is weakened, it becomes loose and a strong weakening of the dough is observed during proofing. This is the basis for reducing the duration of dough ripening. As a result of the research, a recipe for "Cheese" bread was developed, which has an extended shelf life and a lower value of crumb porosity, compared to the control by 21.8% – in the case of storage for 72 hours and provides the human body’s need (women aged 18–29 years, I group of labor intensity) for proteins by 14.3% and fats 2 times more compared to the control sample. Встановлено, що порошкоподібний голландський сир характеризується хорошою швидкістю розчинення, низькою схильністю до грудоутворення та показником білизни, що відповідає борошну вищого ґатунку. Хімічний склад сухого твердого сиру представлений переважно білком та жиром, що сприятиме збагаченню хлібобулочних виробів молочними білками та молочним жиром. Встановлено, що за комплексним показником якості оптимальне дозування порошкоподібного голландського сиру в рецептурі хліба з пшеничного борошна становить 4,0% від маси борошна. При такому дозуванні відзначається яскравий колір скоринки виробу та світліший колір м’якушки порівняно з контролем. Хліб набуває приємного вершкового смаку та аромату. Встановлено, що у разі дозування порошкоподібного голландського сиру в кількості 4,0% до маси борошна процес бродіння посилюється, послаблюється клейковина, вона стає пухкою та спостерігається сильне ослаблення тіста під час вистоювання. Це є основою для скорочення тривалості дозрівання тіста. В результаті дослідження розроблено рецептуру хліба «Сирний», який має подовжений термін зберігання та нижче значення пористості м’якушки порівняно з контролем на 21,8% – у разі зберігання протягом 72 годин та забезпечує потребу організму людини (жінки віком 18–29 років, I група інтенсивності праці) у білках на 14,3% та жирах у 2 рази більше порівняно з контрольним зразком.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; сир голландський порошкоподібний; Dutch cheese powder; хліб Сирний